Analysis of Intrinsic Elements in the Novel “Makrifat Cinta” by Candra Malik: Structuralism Theory - Sunarno, Sunarno; Supratno, Haris; Subandiyah, Heny (International Journal of Emerging Research and Review, 2025)
Objective: This research aims to analyze the intrinsic elements in the novel Makrifat Cinta by Candra Malik, focusing on how these elements interact to convey Sufi values, while also situating them within the broader context of literary discourse. Method: This research employs a qualitative descriptive method with a structuralism approach. The analysis was conducted systematically in several stages, beginning with the identification of the intrinsic elements in the novel, including theme, plot, characters, point of view, and language style. Results: The results of the analysis show that the main theme of this novel is the spiritual journey of humans to know God through love (mahabbah) as a path to ma'rifah (knowledge of God). The storyline uses a mixed plot, which moves forward and backward, reflecting a non-linear spiritual journey. The characters in the novel represent Sufistic concepts, where the main character places God as the ultimate goal of his life. The point of view used is first person (confession), giving emotional and spiritual depth to the reader. The language style used combines Indonesian with Sufistic terms and symbolic metaphors, emphasizing the deep meaning of the spiritual journey. Novelty: This research lies in the application of Structuralism Theory to examine the connection between the text's structure and the Sufi values presented. This approach offers a valuable contribution to Indonesian literary studies by focusing on the Sufi dimensions, a perspective that is seldom explored in structuralism theory.